Immunobiological properties of sesquiterpene lactones obtained by chemically transformed structural modifications of trilobolide - Harmatha, Juraj; Vokáč, Karel; Buděšínský, Miloš; Zídek, Zdeněk; Kmoníčková, Eva (Fitoterapia, 2015)
Our previous research on immunostimulatory properties of trilobolide and its structurally related natural analogues isolated from Laser trilobum (L.) Borkh., encouraged us to investigate structurally related guaianolides belonging to a specific group of sesquiterpene lactones with characteristic glycol moiety attached to the lactone ring. Ever increasing attention has been paid to certain guaianolides such as thapsigargin and trilobolide for their promising anti-inflammatory, anticancer, anti-infectious and SERCA inhibitory activities. However, due to their alkylation capabilities, they might be cytotoxic. Search for compounds with preserved immunobiological properties and decreased cytotoxicity led us to transform some of their structural features, particularly those related to their side chain functionality. For this reason, we prepared a series of over 20 various deacylated, acyl modified, or relactonized derivatives of trilobolide. The immunobiological effects were screened in vitro using the rat peritoneal cells primed with lipopolysaccharide. Secretion of interferon-γ (IFN-γ), interleukins (IL) IL-1β, IL-6 and tumour necrosis factor-α (TNF-α) were determined by ELISA, and nitric oxide (NO) production by Griess reagent. Relation between the molecular structure and immunobiological activity was investigated. Acetylation at 7-OH and 11-OH positions of the lactone ring, or acyl modification of the guaianolide functionalities (including relactonization) of trilobolide, led to inability to stimulate secretion of cytokines and production of NO. Interestingly, minor structural changes achieved by catalytic hydrogenation or hydrogenolysis retained the original immunoactivity of trilobolide. It can be concluded that several new chemically transformed sesquiterpene lactones resembling the immunobiological properties of trilobolide or thapsigargin were prepared and identified. The implication of the lactone vicinal diol (glycol) moiety, combined with other structure functionality, was confirmed as essential for immune properties of the trilobolide or thapsigargin type of guaianolides.
Keywords: Animals; Female; Cytokines; butyráty; Rats, Wistar; ženské pohlaví; Molecular Structure; cytokiny; Furans; Structure-Activity Relationship; Butyrates; Sesquiterpenes; kultivované buňky; seskviterpeny; furany; laktony; molekulární struktura; Cells, Cultured; peritoneální makrofágy; krysa rodu Rattus; vztahy mezi strukturou a aktivitou; Apiaceae; oxid dusnatý; zvířata; Lactones; Rats; Nitric Oxide; Macrophages, Peritoneal; potkani Wistar